Simulation of multi-cluster fracture propagation by hydraulic fracturing in shale reservoir. Issue 6 (October 2021) - Yuan, Liang; Li, Ben; Mu, Lingyu; Zhang, Kui; Zhou, Zhou
Abstract: China is rich in shale oil resources. With the continuous breakthrough of exploitation technology, shale oil has become an important strategic oil resource in China. As it turns out, Multi-cluster fracturing technology of horizontal well is an efficient method to produce shale oil. However, most of the research on the initiation and propagation of fractures in shale reservoirs is based on numerical simulation. In this paper, through the improved true triaxial hydraulic fracturing physical simulation system, the rock multi-cluster fracturing physical simulation experiment, obtain the fracturing process parameters, and analyze the mechanism of fracture generation. The numerical model of fracture is established to analyze the interfracture interference phenomenon and optimize the segmenting and clustering problem. The results showed that: The larger the fracturing fluid viscosity is within a certain range, the smaller the probability of fracturing fluid leakage is, and the more conducive to the formation of fractures; Cluster spacing has a great influence on fracture propagation. Compared with double clusters, three clusters of fractures are more conducive to forming effective fractures. This paper comprehensively considers the multi-field coupling effect in the fracturing process, deeply understands the mechanical parameters of natural fractures, improves the understanding of the regularity of mechanical parameters of natural fractures under the multi-field coupling effect of fluid-solid-temperature, and provides further guidance for the optimization design of fracturing parameters.